Pathophysiological links, echocardiographic characteristics, and clinical implications of QRS morphology in patients with dilated cardiomyopathy - (:unkn) unknown (My University, 2015)
Heart failure is an important clinical problem worldwide. There is great interest in evaluating the relationship between electrocardiographic variations and dilated cardiomyopathy (DCM) since it has been used as a predictor of increased morbidity and mortality. The presence of fragmentation in the QRS complexes on 12-lead electrocardiogram (ECG) was reported as a marker of depolarization abnormality in patients with DCM. Previous studies have investigated the relation between QRS morphology and DCM. QRS morphology and duration are associated with clinical deterioration and increased mortality in patients with DCM. Although surface ECG provides valuable information on prognosis of these patients, echocardiographic methods have been used for further investigation of patients with DCM. The aim of the present review is to provide an overview of the pathophysiological links, echocardiographic characteristics and clinical implications of QRS morphology in patients with DCM. © 2015, SAGE Publications. All rights reserved.
Keywords: dilated cardiomyopathy; echocardiography; electrocardiography; fragmented QRS; prognosis; QRS morphology